High-throughput sequencing unravels the cell heterogeneity of cerebrospinal fluid in the bacterial meningitis of children - Xiao, Haihan; Xiao, Haijuan; Zhang, Yun; Guo, Lingyun; Dou, Zhenzhen; Liu, Linlin; Zhu, Liang; Feng, Wenya; Liu, Bing; Hu, Bing; Chen, Tianming; Liu, Gang; et al. (Frontiers in Immunology, 2022)
Bacterial meningitis (BM) is a common life-threatening infection in children that occurs in the central nervous system (CNS). The cytologic examination of cerebrospinal fluid (CSF) is a key parameter in the diagnosis of BM, but the heterogeneity of cells in the CSF has not been elucidated, which limits the current understanding of BM neuroinflammation. In this study, CSF samples were collected from numbers of BM patients in different stages of disease progression. Single-cell RNA-sequencing, with additional bulk transcriptome sequencing, was conducted to decipher the characteristics of CSF cells in BM progression. A total of 18 immune cell clusters in CSF were identified, including two neutrophil, two monocyte, one macrophage, four myeloid dendritic cell, five T cell, one natural killer cell, one B cell, one plasmacytoid dendritic cell, and one plasma cell subtype. Their population profiles and dynamics in the initial onset, remission, and recovery stages during BM progression were also characterized, which showed decreased proportions of myeloid cells and increased proportions of lymphoid cells with disease progression. One novel neutrophil subtype, FFAR2+TNFAIP6+ neutrophils, and one novel monocyte subtype, THBS1+IL1B+ monocytes, were discovered, and their quantity changes positively correlated with the intensity of the inflammatory response in the CSF during BM. In addition, the CSF of BM patients with unsatisfactory therapeutic responses presented with different cell heterogeneities compared to the CSF of BM patients with satisfactory therapeutic responses, and their CSF featured altered intercellular communications and increased proportions of type-Ⅱ myeloid dendritic cells and plasmacytoid dendritic cells. Moreover, bulk transcriptome profiles of autologous CSF cells and peripheral blood leukocytes of BM patients showed that the immune cells in these two physiological compartments exhibited distinct immune responses under different onset conditions. In particular, the CSF cells showed high expression of macrophage characteristic genes and low expression of platelet characteristic genes compared with peripheral blood leukocytes. Our study conducted an in-depth exploration of the characteristics of CSF cells in BM progression, which provided novel insights into immune cell engagement in acute CNS infection.